2018
DOI: 10.1007/s10482-018-1106-9
|View full text |Cite
|
Sign up to set email alerts
|

Saccharothrix tharensis sp. nov., an actinobacterium isolated from the Thar Desert, India

Abstract: The taxonomic provenance of a filamentous actinobacterial strain isolated from a desert soil was established using a polyphasic approach. The strain has chemotaxonomic and morphological properties consistent with its classification in the genus Saccharothrix. It forms a distinct branch in the Saccharothrix 16S rRNA gene tree, related to the type strain of Saccharothrix saharensis (96.7%) but was distinguished readily from it using a combination of phenotypic properties. The genotypic and phenotypic data show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
2
0
1
Order By: Relevance
“…A steady flow of filamentous actinobacteria recovered from other nonpolar deserts have been validly named as new species, they include Amycolatopsis desertii (Busarakam et al ), Desertiactinospora gelatinilytica (Saygin et al ), Nakamurella deserti (Liu et al , b), Prauserella isguensis (Saker et al ), Saccharothrix algeriensis (Zitouni et al ), Saccharothrix tharensis (Ibeyaima et al ) and Streptosporangium becharense (Chaouch et al ).…”
Section: Desertsmentioning
confidence: 99%
“…A steady flow of filamentous actinobacteria recovered from other nonpolar deserts have been validly named as new species, they include Amycolatopsis desertii (Busarakam et al ), Desertiactinospora gelatinilytica (Saygin et al ), Nakamurella deserti (Liu et al , b), Prauserella isguensis (Saker et al ), Saccharothrix algeriensis (Zitouni et al ), Saccharothrix tharensis (Ibeyaima et al ) and Streptosporangium becharense (Chaouch et al ).…”
Section: Desertsmentioning
confidence: 99%
“…One siderophore, one melanin, one lanthipeptide, Table 1. Phenotypic characteristics of strain AN110305 T and related species of the family Pseudonocardiaceae Taxa: 1, strain AN110305 T ; 2, Goodfellowiella [21,22]; 3, Umezawaea [53,54]; 4, Kutzneria [55][56][57][58]; 5, Saccharothrix [59][60][61][62][63][64]. Data were from this study unless indicated.…”
Section: Whole Genome Sequence Analysismentioning
confidence: 99%
“…这些放线菌的种类繁多, 所 产生的次级代谢产物较多 [92][93] . 目前研究较多的沙漠放 线菌主要来自于莫哈韦沙漠、蒙古沙漠 [93] 、撒哈拉沙 漠 [94] 、塔尔沙漠 [95] 和塔克拉玛干沙漠 [65] , 其中被称为 "死亡禁区"的阿塔卡马沙漠较受关注 [96] . Alan 等 [47,[97][98] 对阿塔卡马沙漠进行微生物多样性研究时发现, 阿塔卡马沙漠富含放线菌资源, 大多数分离出的菌株属 于新的链霉菌菌种或稀有链霉菌属.…”
Section: 沙漠unclassified